2021
DOI: 10.3389/fimmu.2021.675535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Extracellular Cathepsin D Reduces Hepatic Lipid Accumulation and Leads to Mild Changes in Inflammationin NASH Mice

Abstract: Background & AimsThe lysosomal enzyme, cathepsin D (CTSD) has been implicated in the pathogenesis of non-alcoholic steatohepatitis (NASH), a disease characterised by hepatic steatosis and inflammation. We have previously demonstrated that specific inhibition of the extracellular CTSD leads to improved metabolic features in Sprague-Dawley rats with steatosis. However, the individual roles of extracellular and intracellular CTSD in NASH are not yet known. In the current study, we evaluated the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In line with these findings, autophagy-related proteins were also decreased in the liver of obese mice (Yang et al, 2010;Tong et al, 2019). On the other hand, extracellular CTSD function is relevant in the accumulation of hepatic lipids and intracellular CTSD is involved in essential processes, such as mitochondrial oxidative phosphorylation and electron transport function (Yadati et al, 2021). Recently, it was described that administration of the extracellular CTSD inhibitor reduced hepatic triglyceride levels in mice fed with a HFD, whereas intracellular or the extracellular CTSD inhibitor decreased hepatic cholesterol levels (Yadati et al, 2021).…”
Section: Role Of Cathepsins and Autophagy In Obesitysupporting
confidence: 69%
See 1 more Smart Citation
“…In line with these findings, autophagy-related proteins were also decreased in the liver of obese mice (Yang et al, 2010;Tong et al, 2019). On the other hand, extracellular CTSD function is relevant in the accumulation of hepatic lipids and intracellular CTSD is involved in essential processes, such as mitochondrial oxidative phosphorylation and electron transport function (Yadati et al, 2021). Recently, it was described that administration of the extracellular CTSD inhibitor reduced hepatic triglyceride levels in mice fed with a HFD, whereas intracellular or the extracellular CTSD inhibitor decreased hepatic cholesterol levels (Yadati et al, 2021).…”
Section: Role Of Cathepsins and Autophagy In Obesitysupporting
confidence: 69%
“…On the other hand, extracellular CTSD function is relevant in the accumulation of hepatic lipids and intracellular CTSD is involved in essential processes, such as mitochondrial oxidative phosphorylation and electron transport function (Yadati et al, 2021). Recently, it was described that administration of the extracellular CTSD inhibitor reduced hepatic triglyceride levels in mice fed with a HFD, whereas intracellular or the extracellular CTSD inhibitor decreased hepatic cholesterol levels (Yadati et al, 2021). With these results the authors concluded that extracellular CTSD is involved in pathways related to lipids and inflammation.…”
Section: Role Of Cathepsins and Autophagy In Obesitymentioning
confidence: 99%
“…S10). Inflammation and oxidative stress are important drivers for NAFLD disease progression [ 27 , 43 , 44 ]. Our data showed that hepatocyte-specific deficiency of HuR significantly increased the expression of macrophage markers, various chemokines, innate immune responses markers, and chemokines in the livers of HuR hKO mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme cathepsin D (CTSE) is a lysosomal enzyme and an indicator of NASH [ 60 ]. CTSE inhibitors can be regarded as promising and safe NASH drugs [ 61 ]. The gene DMBT1 harbors homozygous deletions and/or lacks expression in malignant human brain tumors, and it was named deleted in malignant brain tumors 1 (Dmbt1) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%